Hepatectomy for hepatocellular carcinoma after perioperative management of portal hypertension. Issue 8 (16th April 2019) - Takemura, N.; Aoki, T.; Hasegawa, K.; Kaneko, J.; Arita, J.; Akamatsu, N.; Makuuchi, M.; Kokudo, N.
Abstract : Background: Indications for hepatectomy in patients with hepatocellular carcinoma (HCC) who have portal hypertension (PH) have been controversial. Some studies have concluded that PH is a contraindication to hepatectomy, whereas others have suggested that perioperative prophylactic management (PPM) can help overcome complications after hepatectomy associated with PH. The objective of this retrospective study was to assess the short‐ and long‐term outcomes after hepatectomy for HCC in patients with PH, with or without PPM. Methods: Records were reviewed of consecutive patients who underwent hepatectomy for HCC, with or without PPM of PH, in a single institution from 1994 to 2015. Patients were divided into three groups: those who received PPM for PH (PPM group), patients who had PH but did not receive PPM (no‐PPM group) and those without PH (no‐PH group). Results: A total of 1259 patients were enrolled, including 123 in the PPM group, 181 in the no‐PPM group and 955 in the no‐PH group. Three‐ and 5‐year overall survival rates were 74·3 and 53·1 per cent respectively in the PPM group, 69·2 and 54·9 per cent in the no‐PPM group, and 78·1 and 64·2 per cent in the no‐PH group ( P  = 0·520 for PPM versus no PPM, P  = 0·027 for PPM versus no PH, and P  < 0·001 for no PPM versus no PH). Postoperative morbidity and mortality rates were 26·0 and 0·8 per cent respectively in the PPM group, 29·8 and 1·1 per cent in the no‐PPM group, and 20·3 and 0 per cent in the no‐PH group. Conclusion: The present study has demonstrated acceptable outcomes among patients with HCC who received appropriate management for PH in an Asian population. Enhancement of the safety of hepatic resection through use of PPM may provide a rationale for expansion of indications for hepatectomy in patients with PH. Abstract : This study clarified the prognosis after hepatectomy in patients with hepatocellular carcinoma and portal hypertension. Enhancement of the safety of hepatic resection through use of perioperative prophylactic management may provide a rationale for expansion of indications for hepatectomy in patients with portal hypertension. Portal hypertension is not a contraindication